WAYS TO IMPROVE THE VALUE CHAIN ​​IN DRIED FRUIT EXPORT BASED ON MARKETING STRATEGIES (Marketing Journal, 2025)
This study analyzes marketing approaches aimed at enhancing the efficiency of the value chain in dried fruit exports. Each stage – from raw material production to final export – is evaluated separately, determining the level of value added. Based on global practices, key challenges and recommended marketing strategies are systematized. The analysis reveals that branding, packaging, logistics, and market information play a direct role in improving chain performance.
Keywords: value chain; dried fruits; marketing strategy; export; branding; market integration; packaging